A bismuth modified graphite felt, a preparation method and application thereof

CN122696700BActive Publication Date: 2026-10-09HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611196747.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-09
Estimated Expiration
2046-08-07

AI Technical Summary

Technical Problem

[0002]目前广泛使用的石墨毡电极具有优良的化学、机械稳定性和较低的成本,可以耐受全钒液流电池的电解液强酸性环境和流动压力,但是低比表面积和对钒离子氧化还原反应的缓慢动力学,严重影响了电极的催化活性

Benefits of technology

所述铋改性石墨毡电极在所述钒电池中的电压效率不低于87.9%;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122696700B_ABST
    Figure CN122696700B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of electrodes of all-vanadium redox flow batteries, and discloses a bismuth-modified graphite felt electrode as well as a preparation method and application thereof. In a nitrogen atmosphere, triphenyl bismuth is used as a bismuth source, a precursor is formed by polymerization reaction of triphenyl bismuth, an aromatic monomer and cyanuric chloride in a nitrogen atmosphere, and a carbon-coated bismuth composite material is prepared through high-temperature carbonization; then the composite material is blended and dispersed with a perfluorosulfonic acid solution, graphite felt is impregnated, and an electric reduction treatment is performed to obtain the bismuth-modified graphite felt electrode. The bismuth is introduced into the electrode material in the form of triphenyl bismuth, so that the bismuth is more uniformly distributed in the electrode material, the electrode catalytic V 3+ / V 2+ ability can be effectively improved, the vanadium battery negative electrode reaction kinetics can be accelerated, the hydrogen evolution side reaction of the negative electrode can be reduced, and meanwhile, the nitrogen element is doped by adding cyanuric chloride as a crosslinking agent in the reaction, the electrochemical activity of the material is improved, and thus the efficiency and capacity retention rate of the vanadium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vanadium redox flow battery electrode technology, and particularly to a bismuth-modified graphite felt, its preparation method, and its application. Background Technology

[0002] Currently, widely used graphite felt electrodes possess excellent chemical and mechanical stability and low cost, and can withstand the strongly acidic electrolyte environment and flow pressure of vanadium redox batteries. However, their low specific surface area and slow kinetics of vanadium ion redox reactions severely affect the electrode's catalytic activity. Therefore, improving the activity of graphite felt electrodes and accelerating V... 3+ / V 2+ Understanding redox reaction kinetics, and thus improving battery energy efficiency, is a challenge in electrode material research. Summary of the Invention

[0003] The purpose of this invention is to provide a bismuth-modified graphite felt, its preparation method, and its application, so as to overcome the shortcomings of the prior art.

[0004] This invention provides the following technical solution: In a first aspect, a method for preparing a bismuth-modified graphite felt electrode is disclosed, comprising the following steps: Step S1: In a nitrogen atmosphere, triphenylbismuth, aromatic monomers, and cyanuric chloride are dissolved in acetone, and anhydrous aluminum chloride is added to react. After the reaction is completed, concentrated hydrochloric acid is added and stirred. After centrifugation, washing, drying and heat treatment, carbon-coated bismuth composite material is obtained. Step S2: Disperse the carbon-coated bismuth composite material and perfluorosulfonic acid solution in anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, dry it, and then perform electrochemical reduction treatment to obtain a bismuth-modified graphite felt electrode.

[0005] In one implementation, in step S1: The mass ratio of the triphenylbismuth, the acetone, the aromatic monomer, the cyanuric chloride, the anhydrous aluminum chloride, and the concentrated hydrochloric acid is (1~5):400:(10~20):(5~10):(80~100):(5~50).

[0006] By introducing bismuth through the reaction of triphenylbismuth, aromatic monomers, and cyanuric chloride to form a hypercrosslinked composite polymer, the bismuth can be more uniformly distributed in the electrode material, effectively improving the electrode's catalytic performance. 3+ / V 2+The ability to accelerate the reaction kinetics of the vanadium battery anode and reduce the hydrogen evolution side reaction of the anode is improved, thereby enhancing the performance of the vanadium battery. At the same time, the addition of cyanuric chloride as a crosslinking agent enables nitrogen doping, which improves the electrochemical activity of the material, thereby enhancing the coulombic efficiency, energy efficiency, voltage efficiency and capacity retention of the vanadium battery.

[0007] In one implementation, in step S1: The aromatic monomers are selected from at least one of benzene, biphenyl, triphenylbenzene, and mesitylene.

[0008] In one implementation, in step S1: The reaction temperature for adding anhydrous aluminum chloride is 30~40℃, and the reaction time is 12~24h; The aromatic monomers are selected from at least one of benzene, biphenyl, triphenylbenzene, and mesitylene.

[0009] In one implementation, in step S1: The drying temperature is 50~70℃, and the time is 6~10h.

[0010] The heat treatment atmosphere is nitrogen, the heating rate is 5~10℃ / min, the holding temperature is 550~650℃, and the time is 2~4h.

[0011] In one implementation, in step S2: The mass ratio of the carbon-coated bismuth composite material, the perfluorosulfonic acid solution, and the anhydrous ethanol is (5~8):(3~5):(87~92); The perfluorosulfonic acid solution has a mass fraction of 5%.

[0012] A modification layer synergistically constructed from bismuth-coated composite material and perfluorosulfonic acid solution, after electroreduction treatment, stably loads bismuth species in metallic and low-valence oxide forms onto the graphite felt surface. Simultaneously, the perfluorosulfonic acid resin enhances the interfacial bonding between the active material and the carbon fibers. This structure exhibits excellent mechanical and electrochemical stability during long-term charge-discharge cycles, effectively preventing active material peeling and ensuring the long-term reliability of the electrode operation.

[0013] In one implementation, in step S2: The electrochemical reduction treatment conditions are as follows: using impregnated graphite felt as the working electrode, platinum wire as the counter electrode, and mercury-mercurous sulfate electrode as the reference electrode, the electrochemical reduction treatment is carried out in a mixed electrolyte containing 0.1 mol / L nitric acid and 0.5 mol / L potassium nitrate, and cyclic voltammetry is used to scan at a scan rate of 50 mV / s for 10 min in the voltage range of -0.7 to 0.1 V.

[0014] Electroreduction can reduce bismuth atoms to elemental bismuth, which can then be loaded onto the electrode material in situ, effectively improving the material's stability and catalytic activity.

[0015] Secondly, a bismuth-modified graphite felt electrode is disclosed, which is prepared using the preparation method described above.

[0016] In one embodiment, the surface of the bismuth-modified graphite felt electrode is loaded with a carbon-coated bismuth composite material, and the bismuth species in the carbon-coated bismuth composite material are distributed in situ on the surface and inside the pores of the graphite felt fibers in the form of metallic and low-valence oxides.

[0017] Thirdly, an application of a bismuth-modified graphite felt electrode is disclosed, wherein the bismuth-modified graphite felt electrode prepared by the above-described method or the bismuth-modified graphite felt electrode described above is applied to vanadium batteries; wherein... The bismuth-modified graphite felt electrode has a coulombic efficiency of not less than 97.4% in the vanadium battery. The bismuth-modified graphite felt electrode has an energy efficiency of no less than 85.7% in the vanadium battery; The voltage efficiency of the bismuth-modified graphite felt electrode in the vanadium battery is not less than 87.9%; The bismuth-modified graphite felt electrode retains a capacity of no less than 94.7% after 100 cycles in the vanadium battery.

[0018] The beneficial effects of the present invention include at least the following: 1. Under nitrogen protection, triphenylbismuth, aromatic monomers, and cyanuric chloride can form a hypercrosslinked composite polymer, achieving in-situ doping of bismuth atoms. High-temperature carbonization then forms a carbon-coated structure, effectively inhibiting the aggregation and loss of bismuth particles during heat treatment and subsequent electrochemical processes. The carbon layer not only confines the bismuth particles but also improves the conductivity of the composite material, ensuring a uniform distribution of bismuth active sites on the surface and within the pores of the graphite felt, significantly enhancing the electrode's catalytic activity for the redox reaction of vanadium ions. 2. The modification layer, synergistically constructed from carbon-coated bismuth composite material and Nafion dispersion, after electroreduction treatment, stably loads bismuth species in metallic and low-valence oxide forms onto the graphite felt surface. Simultaneously, Nafion resin enhances the interfacial bonding between the active material and the carbon fibers. This structure exhibits excellent mechanical and electrochemical stability during long-term charge-discharge cycles, effectively preventing active material peeling and ensuring the long-term reliability of the electrode operation. 3. Introducing bismuth through triphenylbismuth allows for a more uniform distribution of bismuth in the electrode material, effectively enhancing the electrode's catalytic activity. 3+ / V 2+The ability to accelerate the reaction kinetics of the vanadium battery anode and reduce the hydrogen evolution side reaction of the anode is improved, thereby enhancing the performance of the vanadium battery. At the same time, the addition of cyanuric chloride as a crosslinking agent enables nitrogen doping, which improves the electrochemical activity of the material, thereby enhancing the coulombic efficiency, energy efficiency, voltage efficiency and capacity retention of the vanadium battery. Attached Figure Description

[0019] Figure 1 This is a SEM image of the carbon-coated bismuth composite material prepared in Example 1 of this invention. Detailed Implementation

[0020] The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0021] A method for preparing a bismuth-modified graphite felt electrode includes the following steps: Step S1: Under a nitrogen atmosphere, triphenylbismuth, aromatic monomers, and cyanuric chloride are added to acetone and stirred to dissolve. Then, anhydrous aluminum chloride is added, and the mixture is stirred at 30-40°C for 12-24 hours. After the reaction is completed, the mixture is cooled to room temperature, concentrated hydrochloric acid is added, and the mixture is centrifuged to obtain a precipitate. The precipitate is washed with acetone and ethanol and dried under vacuum at 50-70°C for 6-10 hours. The dried graphite felt is placed in an atmosphere furnace, and under a nitrogen atmosphere, the temperature is increased to 550-650°C at a rate of 5-10°C / min and held for 2-4 hours to obtain a carbon-coated bismuth composite material. The mass ratio of the triphenylbismuth, acetone, aromatic monomers, cyanuric chloride, anhydrous aluminum chloride, and concentrated hydrochloric acid is (1-5):400:(10-20):(5-10):(80-100):(5-50). The aromatic monomers are benzene, biphenyl, triphenylbenzene, and mesitylene.

[0022] Step S2: The carbon-coated bismuth composite material and a 5% Nafion solution are dispersed in anhydrous ethanol to obtain a mixed solution; the graphite felt is immersed in the mixed solution, removed and dried, and used as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1 mol / L nitric acid and 0.5 mol / L potassium nitrate as the electrolyte. Cyclic voltammetry is used, with a voltage range of -0.7~0.1V, a scan rate of 50mV / s, and a time of 10min for electroreduction to obtain a bismuth-modified graphite felt electrode; the mass ratio of the carbon-coated bismuth composite material, the Nafion solution, and the anhydrous ethanol is (5~8):(3~5):(87~92).

[0023] Example 1: The following technical solution is adopted. Step S1: In a nitrogen atmosphere, 1g of triphenylbismuth, 10g of benzene, and 5g of cyanuric chloride were added to 400g of acetone and stirred to dissolve. Then, 80g of anhydrous aluminum chloride was added, and the mixture was stirred at 35°C for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, and 5g of concentrated hydrochloric acid was added and stirred. The mixture was centrifuged to obtain a precipitate, which was washed with acetone and ethanol and dried under vacuum at 60°C for 8 hours. The dried graphite felt was placed in an atmosphere furnace and heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere. The temperature was maintained for 2 hours to obtain a carbon-coated bismuth composite material.

[0024] Step S2: Disperse 5g of the carbon-coated bismuth composite material and 3g of 5% Nafion solution in 87g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove and dry it, and use it as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1mol / L nitric acid and 0.5mol / L potassium nitrate as the electrolyte. Use cyclic voltammetry, set the voltage range to -0.7~0.1V, the scan rate to 50mV / s, and the time to 10min, to perform electroreduction to obtain the bismuth-modified graphite felt electrode.

[0025] like Figure 1 The image shown is an SEM image of the carbon-coated bismuth composite material prepared in this embodiment. It can be seen that the carbon layer contains particulate matter, indicating that bismuth is encapsulated inside by porous carbon.

[0026] Example 2: The following technical solution is adopted. Step S1: In a nitrogen atmosphere, 5g of triphenylbismuth, 20g of biphenyl, and 10g of cyanuric chloride were added to 400g of acetone and stirred to dissolve. Then, 100g of anhydrous aluminum chloride was added, and the mixture was stirred at 30°C for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, and 50g of concentrated hydrochloric acid was added and stirred. The precipitate was obtained by centrifugation, washed with acetone and ethanol, and dried under vacuum at 50°C for 6 hours. The dried graphite felt was placed in an atmosphere furnace and heated to 650°C at a heating rate of 10°C / min under a nitrogen atmosphere and held for 4 hours to obtain carbon-coated bismuth composite material.

[0027] Step S2: Disperse 8g of the carbon-coated bismuth composite material and 5g of 5% Nafion solution in 92g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove and dry it, and use it as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1mol / L nitric acid and 0.5mol / L potassium nitrate as the electrolyte. Use cyclic voltammetry, set the voltage range to -0.7~0.1V, the scan rate to 50mV / s, and the time to 10min, to perform electroreduction to obtain the bismuth-modified graphite felt electrode.

[0028] Example 3: The following technical solution is adopted. Step S1: In a nitrogen atmosphere, 3g of triphenylbismuth, 15g of triphenylbenzene, and 7g of cyanuric chloride were added to 400g of acetone and stirred to dissolve. Then, 90g of anhydrous aluminum chloride was added, and the mixture was stirred at 40°C for 18h. After the reaction was completed, the mixture was cooled to room temperature, and 30g of concentrated hydrochloric acid was added and stirred. The precipitate was obtained by centrifugation, washed with acetone and ethanol, and dried under vacuum at 70°C for 10h. The dried graphite felt was placed in an atmosphere furnace, and under a nitrogen atmosphere, the temperature was increased to 600°C at a rate of 8°C / min and held for 3h to obtain carbon-coated bismuth composite material.

[0029] Step S2: Disperse 7g of the carbon-coated bismuth composite material and 4g of 5% Nafion solution in 90g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove and dry it, and use it as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1mol / L nitric acid and 0.5mol / L potassium nitrate as the electrolyte. Use cyclic voltammetry, set the voltage range to -0.7~0.1V, the scan rate to 50mV / s, and the time to 10min, to perform electroreduction to obtain the bismuth-modified graphite felt electrode.

[0030] Example 4: The following technical solution is adopted. Step S1: In a nitrogen atmosphere, 5g of triphenylbismuth, 18g of mesitylene, and 8g of cyanuric chloride were added to 400g of acetone and stirred to dissolve. Then, 100g of anhydrous aluminum chloride was added, and the mixture was stirred at 35°C for 24h. After the reaction was completed, the mixture was cooled to room temperature, and 40g of concentrated hydrochloric acid was added and stirred. The precipitate was obtained by centrifugation, washed with acetone and ethanol, and dried under vacuum at 60°C for 8h. The dried graphite felt was placed in an atmosphere furnace, and under a nitrogen atmosphere, the temperature was increased to 600°C at a rate of 10°C / min and held for 4h to obtain carbon-coated bismuth composite material.

[0031] Step S2: Disperse 8g of the carbon-coated bismuth composite material and 5g of 5% Nafion solution in 92g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove and dry it, and use it as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1mol / L nitric acid and 0.5mol / L potassium nitrate as the electrolyte. Use cyclic voltammetry, set the voltage range to -0.7~0.1V, the scan rate to 50mV / s, and the time to 10min, to perform electroreduction to obtain the bismuth-modified graphite felt electrode.

[0032] Comparative Example 1: The following technical solution is adopted. The only difference from Example 1 is that bismuth powder is used instead of triphenylbismuth in step S1.

[0033] Step S1: In a nitrogen atmosphere, 0.47g of bismuth powder, 10g of benzene, and 5g of cyanuric chloride were added to 400g of acetone and stirred to dissolve. Then, 80g of anhydrous aluminum chloride was added, and the mixture was stirred at 35°C for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, and 5g of concentrated hydrochloric acid was added and stirred. The mixture was centrifuged to obtain a precipitate, which was washed with acetone and ethanol and dried under vacuum at 60°C for 8 hours. The dried graphite felt was placed in an atmosphere furnace and heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere. The temperature was maintained for 2 hours to obtain a carbon-coated bismuth composite material.

[0034] Step S2: Disperse 5g of the carbon-coated bismuth composite material and 3g of 5% Nafion solution in 87g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove and dry it, and use it as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1mol / L nitric acid and 0.5mol / L potassium nitrate as the electrolyte. Use cyclic voltammetry, set the voltage range to -0.7~0.1V, the scan rate to 50mV / s, and the time to 10min, to perform electroreduction to obtain the bismuth-modified graphite felt electrode.

[0035] Comparative Example 2: The following technical solution is adopted. The only difference from Example 1 is that no aromatic monomers are involved in step S1.

[0036] Step S1: In a nitrogen atmosphere, 1g of triphenylbismuth and 5g of cyanuric chloride were added to 400g of acetone and stirred to dissolve. Then, 80g of anhydrous aluminum chloride was added and stirred at 35°C for 12h. After the reaction was completed, the mixture was cooled to room temperature, 5g of concentrated hydrochloric acid was added and stirred, and centrifuged to obtain a precipitate. The precipitate was washed with acetone and ethanol and dried under vacuum at 60°C for 8h. The dried graphite felt was placed in an atmosphere furnace and heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere and held for 2h to obtain a carbon-coated bismuth composite material.

[0037] Step S2: Disperse 5g of the carbon-coated bismuth composite material and 3g of 5% Nafion solution in 87g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove and dry it, and use it as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1mol / L nitric acid and 0.5mol / L potassium nitrate as the electrolyte. Use cyclic voltammetry, set the voltage range to -0.7~0.1V, the scan rate to 50mV / s, and the time to 10min, to perform electroreduction to obtain the bismuth-modified graphite felt electrode.

[0038] Comparative Example 3: The following technical solution is adopted. The only difference from Example 1 is that cyanuric chloride is not involved in step S1.

[0039] Step S1: In a nitrogen atmosphere, 1g of triphenylbismuth and 10g of benzene were added to 400g of acetone and stirred to dissolve. Then, 80g of anhydrous aluminum chloride was added and stirred at 35°C for 12h. After the reaction was completed, the mixture was cooled to room temperature, 5g of concentrated hydrochloric acid was added and stirred, and centrifuged to obtain a precipitate. The precipitate was washed with acetone and ethanol and dried under vacuum at 60°C for 8h. The dried graphite felt was placed in an atmosphere furnace and heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere and held for 2h to obtain a carbon-coated bismuth composite material.

[0040] Step S2: Disperse 5g of the carbon-coated bismuth composite material and 3g of 5% Nafion solution in 87g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove and dry it, and use it as the working electrode, with a platinum wire as the counter electrode, a mercury-mercurous sulfate electrode as the reference electrode, and a mixed solution containing 0.1mol / L nitric acid and 0.5mol / L potassium nitrate as the electrolyte. Use cyclic voltammetry, set the voltage range to -0.7~0.1V, the scan rate to 50mV / s, and the time to 10min, to perform electroreduction to obtain the bismuth-modified graphite felt electrode.

[0041] Comparative Example 4: The following technical solution is adopted. The only difference from Example 1 is that no electrical reduction is performed in step S2.

[0042] Step S1: In a nitrogen atmosphere, 1g of triphenylbismuth, 10g of benzene, and 5g of cyanuric chloride were added to 400g of acetone and stirred to dissolve. Then, 80g of anhydrous aluminum chloride was added, and the mixture was stirred at 35°C for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, and 5g of concentrated hydrochloric acid was added and stirred. The mixture was centrifuged to obtain a precipitate, which was washed with acetone and ethanol and dried under vacuum at 60°C for 8 hours. The dried graphite felt was placed in an atmosphere furnace and heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere. The temperature was maintained for 2 hours to obtain a carbon-coated bismuth composite material.

[0043] Step S2: Disperse 5g of the carbon-coated bismuth composite material and 3g of 5% Nafion solution in 87g of anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, remove it and dry it to obtain a bismuth-modified graphite felt electrode.

[0044] Comparative Example 5: The following technical solution is adopted. Use untreated blank graphite felt.

[0045] The graphite felts prepared in Examples 1-4 and Comparative Examples 1-5 were assembled into fuel cell stacks and subjected to charge-discharge cycle tests under the same operating conditions. The coulombic efficiency, energy efficiency, voltage efficiency, and capacity retention after 100 cycles were recorded. The test results are shown in Table 1. Table 1 Battery performance test results

[0046] As shown in Table 1, compared with Comparative Example 1, Examples 1-4 exhibit higher coulombic efficiency, energy efficiency, voltage efficiency, and capacity retention after 100 cycles. This is mainly due to the more uniform distribution of bismuth in the electrode material achieved by introducing bismuth through triphenylbismuth, which effectively enhances the electrode catalytic efficiency. 3+ / V 2+ The ability to accelerate the kinetics of the vanadium battery anode reaction and reduce the hydrogen evolution side reaction at the anode is improved, thereby enhancing the performance of the vanadium battery. Compared with Comparative Examples 2, 3, and 5, Examples 1-4 exhibit higher coulombic efficiency, energy efficiency, voltage efficiency, and capacity retention after 100 cycles. This is mainly due to the formation of a hypercrosslinked composite polymer by triphenylbismuth, aromatic monomers, and cyanuric chloride under nitrogen protection, achieving doping of bismuth and nitrogen atoms. High-temperature carbonization forms a carbon-coated structure, effectively suppressing the aggregation and loss of bismuth particles during heat treatment and subsequent electrochemical processes. The carbon layer not only acts as a confinement layer but also improves the conductivity of the composite material, ensuring that bismuth active sites are uniformly distributed on the surface and within the pores of the graphite felt. This significantly enhances the catalytic activity of the electrode for the redox reaction of vanadium ions, thereby improving the performance of the vanadium battery. Compared to Comparative Example 4, Examples 1-4 exhibit higher coulombic efficiency, energy efficiency, voltage efficiency, and capacity retention after 100 cycles. This is mainly because electroreduction enables bismuth atoms to be reduced to elemental bismuth and loaded onto the electrode material in situ, effectively improving the material's stability and catalytic activity.

[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a bismuth-modified graphite felt electrode, characterized in that, Includes the following steps: Step S1: In a nitrogen atmosphere, triphenylbismuth, aromatic monomers, and cyanuric chloride are dissolved in acetone, and anhydrous aluminum chloride is added to react. After the reaction is completed, concentrated hydrochloric acid is added and stirred. After centrifugation, washing, drying and heat treatment, carbon-coated bismuth composite material is obtained. Step S2: Disperse the carbon-coated bismuth composite material and perfluorosulfonic acid solution in anhydrous ethanol to obtain a mixed solution; immerse the graphite felt in the mixed solution, dry it, and then perform electrochemical reduction treatment to obtain a bismuth-modified graphite felt electrode.

2. The preparation method according to claim 1, characterized in that, In step S1: The mass ratio of the triphenylbismuth, the acetone, the aromatic monomer, the cyanuric chloride, the anhydrous aluminum chloride, and the concentrated hydrochloric acid is (1~5):400:(10~20):(5~10):(80~100):(5~50).

3. The preparation method according to claim 1, characterized in that, In step S1: The aromatic monomers are selected from at least one of benzene, biphenyl, triphenylbenzene, and mesitylene.

4. The preparation method according to claim 1, characterized in that, In step S1: The reaction temperature for adding anhydrous aluminum chloride is 30~40℃, and the reaction time is 12~24h; The aromatic monomers are selected from at least one of benzene, biphenyl, triphenylbenzene, and mesitylene.

5. The preparation method according to claim 1, characterized in that, In step S1: The drying temperature is 50~70℃, and the time is 6~10h; The heat treatment atmosphere is nitrogen, the heating rate is 5~10℃ / min, the holding temperature is 550~650℃, and the time is 2~4h.

6. The preparation method according to claim 1, characterized in that, In step S2: The mass ratio of the carbon-coated bismuth composite material, the perfluorosulfonic acid solution, and the anhydrous ethanol is (5~8):(3~5):(87~92); The perfluorosulfonic acid solution has a mass fraction of 5%.

7. The preparation method according to claim 1, characterized in that, In step S2: The electrochemical reduction treatment conditions are as follows: using impregnated graphite felt as the working electrode, platinum wire as the counter electrode, and mercury-mercurous sulfate electrode as the reference electrode, the electrochemical reduction treatment is carried out in a mixed electrolyte containing 0.1 mol / L nitric acid and 0.5 mol / L potassium nitrate, and cyclic voltammetry is used to scan at a scan rate of 50 mV / s for 10 min in the voltage range of -0.7 to 0.1 V.

8. A bismuth-modified graphite felt electrode, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.

9. The bismuth-modified graphite felt electrode as described in claim 8, characterized in that, The surface of the bismuth-modified graphite felt electrode is loaded with carbon-coated bismuth composite material, and the bismuth species in the carbon-coated bismuth composite material are distributed in situ on the surface and inside the pores of the graphite felt fibers in the form of metallic and low-valence oxides.

10. An application of a bismuth-modified graphite felt electrode, characterized in that, The bismuth-modified graphite felt electrode prepared by the method according to any one of claims 1-7, or the bismuth-modified graphite felt electrode according to claims 8-9, is used in a vanadium battery; wherein, The bismuth-modified graphite felt electrode has a coulombic efficiency of not less than 97.4% in the vanadium battery. The bismuth-modified graphite felt electrode has an energy efficiency of no less than 85.7% in the vanadium battery; The voltage efficiency of the bismuth-modified graphite felt electrode in the vanadium battery is not less than 87.9%; The bismuth-modified graphite felt electrode retains a capacity of no less than 94.7% after 100 cycles in the vanadium battery.

Citation Information

Patent Citations

  • Sodium-ion battery negative electrode material as well as preparation method and application thereof

    CN115621452A

  • Multi-stage pore graphite felt for flow battery and preparation method of multi-stage pore graphite felt

    CN121307052A